An Analysis of Renewable Energy Resources (International Journal of Innovative Research in Computer Science & Technology, 2022)
Regardless of fact that earth's form  cannot alteration, world is fast becoming a global  community as world's populace consumes more energy on  a frequent basis. Energy & related services have become  progressively crucial for human economic & social  development, well-being, & healthcare. Turning to  renewable to address climate alteration is a fantastic  concept, but it should be sustained with intention of meeting energy capacity of upcoming generations.  Research examined benefits of renewable sources of  energy, like security of energy, access of energy, socio - economical development, mitigating climate alteration, & reduced health & ecological impacts. Notwithst&ing se  benefits, re are still barriers to renewable energy sources'  long-term sustainability in terms of mitigating climate  alteration. Among se difficulties include market  distortions, deficiency of information, procurement of raw  resources for foreseeable renewable resource deployment,  & everyday carbon impact. Research suggests policies & activities that, if followed, would assistance in attaining  objective of renewable energy, lowering emanations,  dealing with climate alteration, & delivering sterile  atmosphere & clean energy to all present & upcoming  generations.
Keywords: Bioenergy; Hydro Power; Renewable Energy Resources; Solar Energy; Wind Energy